Chemical reactivity and bioactivity properties of pyrazinamide analogs of acetylsalicylic acid and salicylic acid using conceptual density functional theory. Issue 6 (June 2020) - Villagracia, Al Rey; Ong, Hui Lin; Lagua, Faith Marie; Alea, Glenn
Abstract: Conventional drugs used to treat Tuberculosis (TB) are becoming ineffective due to the occurrence of multiple drug resistant strains of tuberculosis (TB). This has made the TB disease a a serious global health dilemma. Hence, there is desperate necessity for the advancement of new drugs. In this work, the chemical reactivity and bioactivity of several analogs ofpyrazinamide (PZA) were investigated. PZA is one of the first-line of drugs used to treat tuberculosis and is a key contributor to shortening the treatment time for the disease. Chemical reactivity descriptors of pyrazinamide (PZA) and its analogs of acetylsalicyclic acid and salicyclic acid were investigated using conceptual density functional theory in water as a solvent at the MN12SX/Def2TZVP level of theory. Results have shown that all PZA analogs have improved their global and local reactivity indeces as compared to pyrazinamide based on its electronegativity, electrodonating power, electroaccepting power, eletrophilicity, global hardness and dual descriptor condensed fukui indexes. Moreover, their pKa values are slightly higher than PZA. In terms of its drug-likeness, all PZA analogs passed the Lipinski's Rule of Five criteria. Furthermore, their bioactivity scores are significantly better than pyrazinamide indicating good reaction to G-Protein Coupled Receptor (GPCR) ligands, kinase inhibitors, ion channel modulators, nuclear receptor ligands, protease inhibitors and other enzyme targets. Overall, the PZA analogs are found to be promising anti-tuberculosis drugs. Based on global and local reactivity descriptors, pKa and bioactivity scores, PZA analog of 5-n-Octanoylsalicylic acid is the most reactive among the PZA analogs tested. Abstract : Theoretical chemistry; Pyrazinamide, Tuberculosis, Density functional theory, Bioactivity, Chemical reactivity.